Sediment quality assessment of Santos shoreline trough toxicity assays and characterization of macrobenthic community structure - Aliceda Ferraz, Mariana; Brasil Choueri, Rodrigo; Ferreira Fiori, Evelyn; Rodrigues Nobre, Caio; Cesar, Augusto; Dias Seabra Pereira, Camilo (O Mundo da Saúde, 2012)
This study evaluated the toxicity of the sediment on 7 points located in front of drainage canals river on the beaches of Santos- SP, together with the characterization of the community structure of benthic macrofauna. Were performed campaign summer (February 2008) and the campaign winter (July 2008). The toxicity tests with sea-urchin Lytechinus variegatus treatments were performed in elutriate and sediment-water interface, as ABNT NBR 15350/2006. The benthic macrofauna wasidentified as Mollusca, Crustacea and Polychaeta, and it was calculated mean density (ind/0,026m²) and Polychaeta dominance. In campaigns for summer and winter treatment sediment-water interface showed toxicity at all points, while the treatment elutriate showed toxicity at points 6 and 7. Polychaeta dominance was negatively correlated (r = -0,56) with granulometry and positively correlated with organic matter for the winter campaign, being some of these species indicators. of polluted and anoxic environments